Significance of Surface Eco-Protection Techniques for Cohesive Soils Slope in Selangor, Malaysia - Suhatril, Meldi; Osman, Normaniza; Azura Sari, Puteri; Shariati, Mahdi; Marto, Aminaton (Geotechnical and geological engineering, 2019)
Rapid infrastructure development in Malaysia especially in Selangor causes drastic change in landscape and clearing of more vegetated areas. This has gradually lead to slope instability problems that causes enormous loss affecting human lives, destruction of property and environment. Thus, conservation practices by incorporating vegetation to enhance slope stability is much needed alternative to the conventional technique of stabilization. Limited studies had been done in discovering the effectiveness of vegetative covers in relation to slope and soil parameters. Hence, in this paper, a parametric study is carried out to discover the relationship between some of the various vegetation species and different soil types as well as slope angles. Conventional limit equilibrium methods are applied in the analysis considering the soil shear strength parameters, unit weight of soil, as well as slope geometry. Typical scenarios of cut-slope along highways in Selangor are simulated in order to obtain comparable results from the stability assessment by means of calculating the factor of safety. The modelling showed that shallow slip failure can be prevented when sufficient number of roots of a certain tensile force interact with the slip plane, increasing the overall factor of safety of the slope. The percentage of FOS increased due to the vegetation effects can reach up to 43% with slope angles ranging between 15° and 25°. Moreover, based on the parametric study, silty soils showed more significance in contributing to the increase in FOS when incorporating vegetation.